Differences in rates of pelvic lymph node dissection in National Comprehensive Cancer Network favorable, unfavorable intermediate- and high-risk prostate cancer across United States SEER registries. (22nd December 2022) - Flammia, Rocco Simone; Hoeh, Benedikt; Chierigo, Francesco; Hohenhorst, Lukas; Sorce, Gabriele; Tian, Zhen; Leonardo, Costantino; Graefen, Markus; Terrone, Carlo; Saad, Fred; Shariat, Shahrokh F.; Briganti, Alberto; et al.
Abstract: Background: The National Comprehensive Cancer Network (NCCN) guidelines recommend pelvic lymph node dissection (PLND) in NCCN high- and intermediate-risk prostate cancer patients. We tested for PLND nonadherence (no-PLND) rates within the Surveillance Epidemiology and End Results (2010–2015). Materials and methods: We identified all radical prostatectomy patients who fulfilled the NCCN PLND guideline criteria (n = 23, 495). Nonadherence rates to PLND were tabulated and further stratified according to NCCN risk subgroups, race/ethnicity, geographic distribution, and year of diagnosis. Results: Overall, the no-PLND rate was 26%; it was 41%, 25%, and 11% in the NCCN intermediate favorable, intermediate unfavorable, and high-risk prostate cancer patients, respectively ( p < 0.001). Over time, the no-PLND rates declined in the overall cohort and within each NCCN risk subgroup. Georgia exhibited the highest no-PLND rate (49%), whereas New Jersey exhibited the lowest (15%). Finally, no-PLND race/ethnicity differences were recorded only in the NCCN intermediate unfavorable subgroup, where Asians exhibited the lowest no-PLND rate (20%) versus African Americans (27%) versus Whites (26%) versus Hispanic-Latinos (25%). Conclusions: The lowest no-PLND rates were recorded in the NCCN high-risk patients followed by NCCN intermediate unfavorable and favorable risk in that order. Our findings suggest that unexpectedly elevated differences in no-PLND rates warrant further examination. In all the NCCN risk subgroups, the no-PLND rates decreased over time.